Knowledge of cervical cancer, Human Papilloma Virus (HPV) and HPV vaccination among primary health care workers in the Mamusa and Naledi sub districs - Ajayi, Adekunle Omoniyi (My University, 2017)
Introduction: Cervical cancer is a very common female cancer; with up to 524,000 cases being diagnosed annually worldwide.1 Human papilloma virus (HPV) has long been established as the causative factor in the development of cervical cancer.2, 3 HPV vaccination has been found to drastically reduce the development of cervical cancer especially if administered to young people before their sexual debut. This study was to assess the knowledge of primary health care workers in the Mamusa and Naledi sub-districts in the North West Province about cervical cancer, HPV and the HPV vaccine. Methods: This was a descriptive cross-sectional study done with 116 primary health care workers using a self-administered questionnaire that was derived from a duet of questionnaires previously used in Poland and Australia. Adequate knowledge of cervical cancer and HPV vaccination meant getting 70% of the questions asked on the subject correctly while a threshold of 80% was used for adequate knowledge of HPV vaccination. All categories of primary health workers were included in the study asides from pharmacists who were excluded. Descriptive statistics, tests of association and logistic regression analysis was used in the study. The survey was done between September to November 2016 following ethics approval from the University of Witwatersrand. Results: 116 participants were involved in this study. The majority were black female professional nurses with diplomas. The mean age of the participants was 36.6 ± 8.7 years. Only 26% of the respondents had adequate knowledge of cervical cancer. 41% of respondents had adequate knowledge of HPV, while 67% of respondents had adequate knowledge about HPV vaccination. In our study, we found a significant association between knowledge of HPV and the health care worker category (p < 0.001). There was a significant association between knowledge of HPV vaccination and the highest educational level that was attained by the respondents (p= 0.010). Conclusion: Primary health care workers form an integral part in the fight against cervical cancer. Significant gaps still exist in the level of knowledge of health care workers, particularly in relation to cervical cancer and HPV. Improved learning and training opportunities for primary health care workers can help correct the knowledge deficit
Research Report submitted to the Faculty of Health Sciences, University of Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Medicine in Family Medicine. Johannesburg, September 2017.
Keywords: Papillomavirus Vaccines; Uterine Cervical Neoplasms; Human Papillomavirus